Development and Comparative In Vitro and In Vivo Study of BNN27 Mucoadhesive Liposomes and Nanoemulsions for Nose-to-Brain Delivery - Maria Kannavou; Kanelina Karali; Theodora Katsila; Eleni Siapi; Antonia Marazioti; Pavlos Klepetsanis; Theodora Calogeropoulou; Ioannis Charalampopoulos; Sophia G. Antimisiaris (MDPI AG, 2023)
Intranasal administration offers an alternative and promising approach for direct nose-to-brain delivery. Herein, we developed two chitosan (CHT)-coated (and uncoated) nanoformulations of BNN27 (a synthetic C-17-spiro-dehydroepiandrosterone analogue), liposomes (LIPs), and nanoemulsions (NEs), and compared their properties and brain disposition (in vitro and in vivo). LIPs were formulated by thin film hydration and coated with CHT by dropwise addition. BNN27-loaded NEs (BNEs) were developed by spontaneous emulsification and optimized for stability and mucoadhesive properties. Mucoadhesive properties were evaluated by mucin adherence. Negatively charged CHT-coated LIPs (with 0.1% CHT/lipid) demonstrated the highest coating efficiency and mucoadhesion. BNEs containing 10% w/w Capmul-MCM and 0.3% w/w CHT demonstrated the optimal properties. Transport of LIP or NE-associated rhodamine-lipid across the blood-brain barrier (in vitro) was significantly higher for NEs compared to LIPs, and the CHT coating demonstrated a negative effect on transport. However, the CHT-coated BNEs demonstrated higher and faster in vivo brain disposition following intranasal administration compared to CHT-LIPs. For both BNEs and LIPs, CHT-coating resulted in the increased (in vivo) brain disposition of BNN27. Current results prove that CHT-coated NEs consisting of compatible nasal administration ingredients succeeded in to delivering more BNN27 to the brain (and faster) compared to the CHT-coated LIPs.